Consumer acceptance and sensory profiling of reengineered kitoza products. (1st May 2016) - Pintado, Ana I.E.; Monteiro, Maria J.P.; Talon, Régine; Leroy, Sabine; Scislowski, Valérie; Fliedel, Geneviève; Rakoto, Danielle; Maraval, Isabelle; Costa, Ana I.A.; Silva, Ana P.; Pallet, Dominique; Tomlins, Keith; et al.
Highlights: Sensory profiles showed differences between the two Kitoza samples. Kitoza beef (KB) showed more intense meat flavour. Kitoza pork (KP) showed more intense sweet odour, spices and smoked odour. Between KB and KP samples, KP showed to be more appreciated. Geographic origin of Kitoza had a positive effect on consumers' willingness to pay. Abstract: Kitoza refers to a traditional way of preparing beef and pork in Madagascar. However, in order to improve some drawbacks previous identified, the product was submitted to a reengineering process. The acceptance and sensory profiling of improved Kitoza products among Portuguese consumers was investigated. A local smoked loin sausage was selected as basis for comparison. Firstly, a Focus Group study was performed to identify sensory descriptors for Kitoza products and explore product perception. Subsequently, a Flash Profile and a consumer sensory acceptance study were conducted. Flash Profile's results showed that beef- and pork-based Kitoza products investigated differed considerably in all sensory dimensions. The Portuguese sausage was characterized as having a more intense and lasting after taste, as well as displaying a higher degree of (meat) doneness. The acceptance study yielded higher overall liking ratings for pork- than for beef-based Kitoza, although the Portuguese sausage remained the most appreciated product.